Shifting linguistic patterns in oyster restoration news articles surrounding the Deepwater Horizon disaster - Fitzsimmons-Doolan, Shannon; Beseres Pollack, Jennifer (Frontiers in Conservation Science, 2023)
Populations of the eastern oyster, Crassostrea virginica, are declining globally. With loss of oysters, sustainable provision of natural resources and ecosystem services are also threatened. In 2010, the Deepwater Horizon (DWH) oil spill became the largest marine oil spill in history, imperiling coastal and marine habitats in the Gulf of Mexico. Whereas ecological restoration serves as an important tool in natural resource management, its success depends on achieving ecological objectives and meeting public expectations. However, little is known about how the public perceives ecological restoration—even less in the context of disasters. It has long been understood that mass media messaging helps shape public understanding. Documenting patterned representation of oyster restoration in mass media texts can help set goals, improve stakeholder communication, and ensure required support for restoration activities. To address this goal, this study asks, Does newspaper language on the topic of oyster reef restoration change in relation to an environmental disaster? If so, how? A 1.1 million-word Deepwater Horizon Oyster Restoration (DHORN) Corpus—a comprehensive body of newspaper articles about oyster restoration from 3 national and 18 gulf-state newspapers—was developed for the period April 2008-April 2014. The distribution and deployment of collocates of OYSTER* across three DHORN subcorpora delimited by time (pre, during, post the Deepwater Horizon oil spill) were compared through iterative quantitative and qualitative analysis. Examination of salient collocates in use over time indicated an increase in the representation of oysters as quantifiable entities during-/post-DWH at the same time that there was a decrease in the representation of the roles of OYSTER* in the Gulf ecosystem. Furthermore, multiple propositions associating oysters and oyster restoration activity with DWH and oil spills were introduced into language use by the disaster and persisted for years afterwards. This association was not present pre-DWH. Understanding shifts in linguistic patterns of oyster restoration in news articles before, during, and after Deepwater Horizon can be used to deliberately refine communication between the conservation community and both journalists and policymakers to promote conservation initiatives.